2010
DOI: 10.4081/or.2010.e9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of post-operative analgesia after posterior lumbar instrumented fusion for degenerative disc disease: a prospective randomized comparison of epidural catheter and intravenous administration of analgesics

Abstract: This prospective study aimed to compare the efficacy of epidural (EDA) versus intravenous (PCA) application of analgesics after lumbar fusion. Fifty-two patients scheduled for elective posterior instrumented lumbar fusion were randomized into two groups. EDA patients received an epidural catheter intraoperatively, and administration of ropivacain and sulfentanil was started after a normal postoperative wake-up test in the recovery room area. PCA patients received intravenous opioids in the post-operative perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…A total of 136 studies were identified from our electronic database searching and manual searching, remaining 9 studies qualified for our meta-analysis [12,27,[39][40][41][42][43][44][45]. Briefly, we excluded studies for duplicates (n = 1), unrequired article types (letters, reviews, non-human studies, unrelated to research topics and meta-analysis; n = 54).…”
Section: Included Studiesmentioning
confidence: 99%
“…A total of 136 studies were identified from our electronic database searching and manual searching, remaining 9 studies qualified for our meta-analysis [12,27,[39][40][41][42][43][44][45]. Briefly, we excluded studies for duplicates (n = 1), unrequired article types (letters, reviews, non-human studies, unrelated to research topics and meta-analysis; n = 54).…”
Section: Included Studiesmentioning
confidence: 99%
“…After spine surgery epidural catheters are difficult to manage and maintain. In addition, there is always a concern of infection, restricting its widespread application [3]. Other investigators have attempted to prolong the duration of analgesic action by morphine-adon L compound, Oxiplex/ SP gel-morphine [10] and Vaseline-Sterile-Oil-Morphine [11] and many of these techniques lack wider applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural catheters are difficult to manage and maintain after spine surgery. In addition, there is always a concern of infection, restricting its widespread application [3]. The easy access to epidural space during laminectomy surgery was utilized safely for applying morphine directly over the exposed dura mater in earlier studies but has limited application due to short duration of action (3-24 h) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Others found that differences in pain relief occurred only after 12 hours, even days after surgery [35,37]. Some authors found that due to the frequent side-effects the epidural route could not be recommended as first line treatment for postoperative analgesia after spine surgery [24, 35,47], while more patients suffered paresthesia with placement of the catheter [25][26][27]. Failure of the epidural modality, need for temporarily or permanent discontinuation of epidural treatment and/or catheter loss while costing significantly more than systemic analgesia were additional reasons for less enthousiasm in certain studies [20,29,34].…”
Section: Epidural Analgesiamentioning
confidence: 99%
“…A limited duration of analgesia should be expected when using substances in single dose application. Others found that differences in pain relief occurred only after 12 hours, even days after surgery [35,37]. Some authors found that due to the frequent side-effects the epidural route could not be recommended as first line treatment for postoperative analgesia after spine surgery [24, 35,47], while more patients suffered paresthesia with placement of the catheter [25][26][27].…”
Section: Epidural Analgesiamentioning
confidence: 99%